The Art of the Clinician - Miguel, MD, Rodríguez-Guerra,; Neelanjana MD, Pandey,; Elina, MD, Shrestha,; Timothy J. MD , Vittorio, (International Journal of Innovative Research in Medical Science, 2021)
Background: The promotion of clinical abilities could represent a significant factor leading the clinicians to in making the correct diagnosis in a timely matter. Case: Our patient is a 42-year-old African male with a history of Hypertension, ESRD on hemodialysis via right-sided Permcath (PC), Mastoidectomy & Right ear surgery due to trauma in childhood, AV Fistula (Needed intervention 4 times) in left upper extremity, admitted due to witnessed seizures in the setting of hypertensive emergency. The patient denied family history and toxic habits. While the patient was at the emergency room, CT head revealed stable curvilinear hyper-attenuation thought to be a thrombosed developmental vein more likely than small subarachnoid hemorrhage. He was loaded with levetiracetam, received Ativan 1mg IV and HD done as per Nephrology. The patient was transferred to the floor he was not in acute distress and was asymptomatic, the cardiovascular (CV) examination showed regular pulse, normal S1, S2, S4+ appreciated with 2/4 diastolic murmur at second right intercostal space (ICS); 2/6 pansystolic murmur at third right intercostal space left parasternal border (LPSB) radiated to the right parasternal border (RPSB) and right mid-clavicular line (MCL); 3/6 systolic murmur at 5LICS MCL radiated to the posterior axillar line (PAL). Point of maximal impulse (PMI) displaced to mid axillar line (MAL). Parasternal heave present; the neurological exam was preserved. Endocarditis was suspected and echocardiogram was expedited, it showed severe aortic regurgitation, 1.60cm x 1.68cm mass in the tip of the catheter in the right atrium, possible vegetation in the tricuspid valve with mild regurgitation, moderate mitral valve regurgitation. Later, staphylococcus epidermidis was identified in blood cultures twice, as well as the culture from the PC. The transesophageal echocardiogram found 2.41 X 0.62 cm mass appears to be a fibrin sheath, possibly remnant of a prior catheter, small perforation in the non-coronary cusp likely in the setting of healed endocarditis. Infectious disease onboard for antibiotic management. Conclusion: The art of the clinician goes beyond the available technology; it could prevent the loss of critical time as well as unnecessary studies, guiding a better assessment and treatment of our patients and potentially improving their outcomes.